A Need Analysis of ESP Materials for Elementary Education Department Students - Suryantari, Hadna (Universitas Pahlawan Tuanku Tambusai, 2026)
This research aims to investigate the need for ESP materials for Elementary Education Department students including students’ target needs and students’ learning needs. A quantitative approach with descriptive emphasis was used as the research design. Participants of the research were the first semester students of Elementary Education Department of University X in the academic year of 2025/2026. A total sampling technique was used in the research. The population was 142 students. A questionnaire was used to find out ESP needs of Elementary Education Department students and it is obtained 128 answers. The data from questionnaire were analyzed by seeing frequency of the participants’ answer. The data were then presented in the form of charts. It is found that the students’ learning target is to enhance their English proficiency, primarily speaking skills and vocabulary mastery for encouraging their future career. Developing the students’ speaking skills, vocabulary mastery, reading skills, and grammar mastery are mainly needed to promote professional performance in the instructional field. English learning materials should provide language input supported by vocabulary lists to strengthen students’ vocabulary mastery and boost their English skills. Learning materials should be compiled with text types around the field of elementary education and designed to direct students in various meaningful and contextual activities which enable the students engaged in collaborative language learning activities. Collaborative learning activities facilitate the students to obtain various feedbacks from their friends and lecturers can monitor the students’ learning progress then provide ongoing feedbacks for the students’ work.